Why introducing a parasitoid of Paropsis charybdis Stål, 1860 (Coleoptera: Chrysomelidae) larvae is expected to enhance biological control of this Eucalyptus pest in New Zealand. Issue 4 (2nd September 2020) - Pugh, Andrew R; Withers, Toni M; Peters, Elise M; Allen, Geoff R; Phillips, Craig B
Abstract: Paropsis charybdis (Coleoptera: Chrysomelidae) has been a major pest of Eucalyptus spp. since invading New Zealand from Australia over 100 years ago. Here, we report on the phenology, egg parasitism and defoliation levels of P. charybdis at two Eucalyptus nitens plantations in the central North Island of New Zealand and assess the establishment prospects and potential impact of a new biological control agent, the larval parasitoid Eadya daenerys . Field monitoring found that 90–100% of first generation P. charybdis eggs emerged, showing that the existing egg parasitoids Enoggera nassaui (Hymenoptera: Braconidae) and Neopolycystus insectifurax (Hymenoptera: Pteromalidae) are ineffective at controlling this generation. Further field monitoring revealed effective control of second generation eggs by E. nassaui and N. insectifurax despite the presence of Baeoanusia albifunicle (Hymenoptera: Encyrtidae), a hyperparasitoid of E. nassaui . Phenology data show that first generation P. charybdis larvae will likely be synchronous with the adult emergence of E. daenerys (Hymenoptera: Braconidae) the new larval endoparasitoid proposed to be introduced from Australia. Climate matching predicts E. daenerys could establish in all areas of New Zealand where P. charybdis impacted Eucalyptus spp. plantations are grown. The addition of a larval endoparasitoid could significantly contribute to the suppression of P. charybdis by decreasing first generation larval survival.